Effect of Supply Chain Integration on Organization Performance:A Mediating Role of Competitive Advantage. An Evidence from Manufacturing Firms in Ethiopia. - Megersa, Gezew; Mesfin LEGESSE (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study aimed to fill a knowledge gap in the literature by examining the effect of SCI on organizational performance with competitive advantage. It used a mixed approach and an explanatory and descriptive research design. The study collected data from both primary and secondary sources and used probability sampling, specifically simple random sampling, to examine the relationship between SCI ingredients and organizational performance. The survey was conducted using self-administered and structured, closed-ended questionnaires that were distributed to respondents. Amos in SPSS was used to evaluate the data. While SEM (structural equation model) analysis was used to characterize the causal influence between and among the dependent and independent variables under inquiry, correlation analysis was used to determine the direction and intensity of the association between variables. According to the study, all SCI components and organizational performance have a positive and statistically significant relationship. Regarding SEM analysis, the study discovered that SCI had a favorable and noteworthy impact on organizational performance and competitive advantage. The study concluded that enhanced organizational performance is a result of the implementation of SCI and competitive advantage. It is advised that businesses consistently apply SCI correctly to enhance performance and obtain a competitive edge.